CRITERIA OF CONSTITUTIONALITY OF AUSTERITY MEASURES IN THE OFFICIAL CONSTITUTIONAL DOCTRINE OF THE REPUBLIC OF LITHUANIA - Žalimas, Dainius (Teisė, 2015)
During the global economic crisis, many European countries faced the necessity to apply the austerity measures that involved the reduction of salaries, pensions and other social benefits paid by a state. Austerity has become a difficult challenge in particular to those states who have declared in their constitutions the social orientation of a state or even a social state. The Republic of Lithuania is one of those states: according to its Constitution, the State of Lithuania is socially oriented, it has to undertake certain commitments to the most vulnerable social groups. Lithuania was one of those states who has suffered from the most negative impact of the economic and financial crisis and who, therefore, has applied the drastic austerity measures. Thus, the Constitutional Court of the Republic of Lithuania had in particular difficult task – while assessing the constitutionality of the austerity measures in the circumstances of a deep economic and financial crisis, to balance different constitutional values: stability of public finances and the social orientation of the State implying guarantees of social and economic rights. Considering this, one can see the experience of the Constitutional Court of the Republic of Lithuania in assessing austerity measures as unique and interesting at the European level. The subject of this article – the official constitutional doctrine formulated by the Constitutional Court of the Republic of Lithuania concerning the so-called austerity measures aiming to manage and to overcome economic and financial crisis within a state. The aim of the research is to identify and analyse the criteria of constitutionality of austerity measures. The research was conducted mostly by applying analytical, systematic, comparative and descriptive research methods. This article analyses the following criteria of constitutionality of austerity measures, which have to be observed respecting human rights and social orientation of the State, as consolidated in the Constitution: constitutionally justifiable basis of austerity measures, their necessity, temporal character, proportionality, as well as due regard to the limits of discretion of the legislature, the principles of social solidarity and non-discrimination, the duty to compensate certain losses. The article focuses on specific features of these criteria as far as they concern austerity measures. For example, the financial assessment of the situation in the State usually does not fall within constitutional jurisdiction; therefore, the Constitutional Court ought to abstain from assessing the compatibility of austerity measures with the first three criteria – constitutionally justifiable basis of austerity measures, their necessity and temporal character, i.e. the Court ought to rely on the assessment of the State economy made by the legislature (and the executive) and not to interfere into the matters of substance and expediency of decisions on economic policy. There are two specific aspects of the principle of proportionality in assessing the constitutionality of austerity measures, as indicated in the article: the first one is the requirement not to distort by the austerity measures the proportions of salaries and pensions established before their reductions; the second one is the requirement not to restrict other constitutional rights than those directly restricted by the austerity measures in question. One can read also about three specific requirements for constitutionality of austerity measures, which follow from the principles of social solidarity and non-discrimination: 1) overall and non-discriminative character of austerity measures; 2) the positive discrimination of the most vulnerable social groups; 3) the austerity measures cannot aim at the establishment of egalitarianism. The main conclusion made in this article is that the criteria of constitutionality of austerity measures, as formulated in the official constitutional doctrine of the Republic of Lithuania, are grounded on the general criteria of legality of the restrictions of human rights, as provided by international law, as well as they are in essence identical to the criteria of constitutionality of austerity measures which have been formulated by other European constitutional courts. Therefore, one may see a certain unity in diversity in this field, i.e. one of the elements of European constitutional identity.